Associated Factors with Biochemical Hypoglycemia during an Oral Glucose Tolerance Test in a Chinese Population. (22nd August 2017) - Cai, Xiaoling; Han, Xueyao; Zhou, Xianghai; Zhou, Lingli; Zhang, Simin; Ji, Linong
Abstract : Aim . To find the association between biochemical hypoglycemia on a 2-hour screening oral glucose tolerance test (OGTT) and insulin resistance. Method . Subjects of this study were sampled from the China National Diabetes and Metabolic Disorders Study that was conducted during 2007 and 2008. Blood samples were drawn at 0, 30, and 120 minutes after the glucose load. Biochemical hypoglycemia was defined as 2-hour glucose < 3.0 mmol/l. Results . In total, 26, 606 participants were included, and 141 participants were diagnosed with biochemical hypoglycemia on a 2-hour OGTT. Compared to participants with normal glucose tolerance (NGT), participants with biochemical hypoglycemia presented with a younger age, lower BMI, lower levels of fasting glucose, and lower levels of 30-minute and 2-hour OGTT glucose. In terms of insulin resistance, participants with biochemical hypoglycemia showed higher levels of Matsuda ISI. In terms of β -cell function, participants with biochemical hypoglycemia showed higher levels of Stumvoll early and late indexes. A multivariate regression analysis indicated that higher levels of Matsuda ISI and higher levels of Stumvoll early and late indexes were associated with biochemical hypoglycemia independently. Conclusion . This study indicated that biochemical hypoglycemia might be associated with lower levels of insulin resistance but higher levels of β -cell function in a Chinese population.